2023
DOI: 10.1096/fj.202201724rr
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance of unraveling mitochondrial pathway alterations in non‐small‐cell lung cancer

Abstract: Early detection, accurate monitoring, and therapeutics are major problems in non-small-cell lung cancer (NSCLC) patients. We identified genomic copy number variation of a unique panel of 40 mitochondria-targeted genes in NSCLCs (GEOGSE #29365). Validation of mRNA expression of these molecules revealed an altered panel of 34 genes in lung adenocarcinomas (LUAD) and 36 genes in lung squamous cell carcinomas (LUSC). In the LUAD subtype (n = 533), we iden-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…In this section, we are going to discuss the spread of COVID-19 due to social interactions and different levels of immunity levels among humans. We know the immune system is the best defense because it supports the body's natural ability to defend against pathogens such as viruses, bacteria, fungi, protozoan, and worms, and resists infections [34,35].…”
Section: Assumption 1 the Following Set Of Assumptions Regarding The ...mentioning
confidence: 99%
“…In this section, we are going to discuss the spread of COVID-19 due to social interactions and different levels of immunity levels among humans. We know the immune system is the best defense because it supports the body's natural ability to defend against pathogens such as viruses, bacteria, fungi, protozoan, and worms, and resists infections [34,35].…”
Section: Assumption 1 the Following Set Of Assumptions Regarding The ...mentioning
confidence: 99%
“…In (8), the first order condition determines α 1 . If all the above conditions are satisfied with h(s) = 1 then, Laplace approximation implies,…”
Section: K Dmentioning
confidence: 99%
“…Methylenetetrahydrofolate dehydrogenase 2 (MTHFD2) is an enzyme that has recently come to the forefront due to its high expression in various cancer types, including non-small cell lung cancer, breast cancer, prostate cancer, and blood cancer [22][23][24][25][26][27]. This enzyme plays a pivotal role in mitochondrial folate one-carbon metabolism and is also referred to as NMDMC (NAD-dependent mitochondrial methylenetetrahydrofolate dehydrogenasecyclohydrolase) [28]. Studies have consistently demonstrated that MTHFD2 is a critical factor in driving cancer cell proliferation, making it a significant contributor to tumor growth and advancement [25,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%